2007
DOI: 10.1177/0269216306075112
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in patients with severe multiple sclerosis: two case reports and a survey among German MS neurologists

Abstract: Due to its chronic and fluctuating time course, multiple sclerosis (MS), thus far, has not been regarded as a focus of palliative care. However, sometimes we are confronted with severely affected MS patients, who suffer from complex medical, physical and psychosocial problems, which are not fully covered by the current health care services. We present two cases of severely affected MS patients we saw in our outpatient MS clinic, and who, we believe, are candidates for palliative care. The first patient, with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…Pain is an important and frequent symptom accompanying multiple sclerosis (Svendsen et al, 2005;Kumpfel et al, 2007). MS pain develops in 50-80% of MS patients, with 30% of those patients describing pain as their worst symptom (Beard et al, 2003).…”
Section: Males and Female Both Exhibit Mechanical Allodynia And Thermmentioning
confidence: 99%
“…Pain is an important and frequent symptom accompanying multiple sclerosis (Svendsen et al, 2005;Kumpfel et al, 2007). MS pain develops in 50-80% of MS patients, with 30% of those patients describing pain as their worst symptom (Beard et al, 2003).…”
Section: Males and Female Both Exhibit Mechanical Allodynia And Thermmentioning
confidence: 99%
“…[11][12][13][14] Psychological support, occupational therapy, speech therapy, and palliative care for this group were all perceived as seriously deficient. 15 It remains difficult to conduct adequate needs assessment, as there is still no single, unambiguous, clear definition for the term 'severe MS.' 16 The most commonly used instrument to evaluate the severity of affectedness, the EDSS (Expanded Disease Status Scale), 17 assesses patients' functional status, referring primarily to restriction of movement, not other symptoms relevant for the severity of MS (e.g., fatigue, depression, pain, visual dysfunction). 18,19 Patients' own subjective definitions of being severely affected fit with the palliative approach, where intervention is guided by the subjective assessment of suffering.…”
mentioning
confidence: 99%
“…More than half of cases of depression among patients with MS go undiagnosed. 6 Our research showed that patients with MS are interested in communicating about issues concerning death and dying, 7,8 especially since the burden of the disease can sometimes produce suicidal ideation 9 as reflected in alarming rates of euthanasia and assisted suicide for patients with MS. 10,11 MS may be complicated by cognitive impairment, swallowing, or speech problems. Managing MS requires assistance from a wide range of health care specialists throughout the patient's life.…”
mentioning
confidence: 99%